Melanin/PEDOT:PSS blend as organic mixed ionic electronic conductor (OMIEC) for sustainable electronics - Nozella, Natan Luis [UNESP]; Lima, João Victor Morais [UNESP]; de Oliveira, Rafael Furlan; Graeff, Carlos Frederico de Oliveira [UNESP] (Royal Society of Chemistry (RSC), 2023)
A new and green blend based on PEDOT:PSS and synthetic melanin is demonstrated as an organic mixed ionic electronic conductor (OMIEC) with enhanced ionic–electronic coupling for organic electrochemical transistors and supercapacitors. Organic mixed ionic–electronic conductors (OMIECs) can efficiently couple and transport ionic and electronic charge species, making them key elements for bioelectronics, neuromorphic computing, soft robotics, and energy storage applications. Here, we have synthesized a water-soluble, bio-inspired ion conductor melanin (Mel) and blended it with benchmark conducting polymer poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) to form a new OMIEC. We explored the potential of Mel/PEDOT:PSS OMIEC blends in two critical device applications: organic electrochemical transistors (OECTs) and supercapacitors (SuperCaps). Mel incorporation into PEDOT:PSS enhances the ionic–electronic coupling when ions from an electrolyte are injected into the material, increasing the volumetric capacitance of PEDOT:PSS films ten-fold. The addition of Mel in PEDOT:PSS also increases the transconductance of OECTs (from 7 ± 1 to 11 ± 3 mS), and the energy and power densities of SuperCaps, from 0.41 ± 0.02 to 0.62 ± 0.01 W h kg −1 and from 119 ± 14 to 190 ± 6 W kg −1 , respectively. This work exploits the fundamental properties, device physics, and technological potential of a new and green OMIEC, ultimately aiming the development of sustainable electronics.